Hydrothermal treatment of yeast cell wall generates potent anti-proliferative agents targeting MCF7 breast cancer cells effectively even under culture conditions separated by a plastic wall - Takanori Kitagawa (PLoS ONE, 2025)
Traditionally, the yeast cell wall (YCW) has limited applications because of its low solubility. To overcome this, a novel method was developed using a hydrothermal reaction to enhance its solubility and decrease its viscosity; this resulted in the production of a soluble form of YCW, known as the YCW treated with hydrothermal reaction (YCW-H), with broader chemical composition. However, the biological impact of YCW-H is unclear, excluding its reported plant growth-promotion by effectively regulating soil microspheres. This study investigated the potential of YCW-H to inhibit MCF-7 breast cancer cell proliferation. YCW-H demonstrated significant anti-proliferative effects on MCF7 cells, reducing cell growth by 58.7% ± 6.9 even when physically separated from the cells by a plastic wall. The observation suggests the presence of a diffusible factor against cell proliferation in YCW-H, a phenomenon not observed in the presence of untreated YCW. Reactive carbon species (RCS) generated during the hydrothermal treatment of YCW could be responsible for the effect. The addition of Fe(III) ions into YCW-H further amplified RCS production and elevated its inhibitory activity by about 10% across the plastic barrier. Radical adduct concentration of H2O in a tube which was incubated in YCW-H was 0.47 μmol/L, indicating that radicals migrated into the water through the plastic wall. The concentration of radical adducts in H2O in a tube exposed to YCW-H with Fe(III) ions further increased to 0.51 μmol/L, indicating that the growth inhibition was correlated with the increased RCS levels. Furthermore, flow cytometry analysis revealed the cytotoxic effects of YCW-H, indicating YCW-H is applicable to cancer therapy. Therefore, the findings highlight the pivotal role of RCS in the YCW-H anti-cancer activity, suggesting its potential as a promising candidate for the development of novel medical devices for cancer treatment.